Bogota within globalization (2007)
This article tackles Bogotá’s situation in terms of economic globalization. It analyses the place of the Colombian capital within the new urban scenario provided by globalization. It tests the hypothesis that contemporaneous economic activity is concentrated in the capital and that it is the key place for financial transactions. Such thesis is put forward by Saskia Sassen in the book called The Global City.